Fresno County Legal Services Honoring Interim Director Janice Pearson - Watkins, Howard::::::::: (1979)
Janice Pearson, Mary Ludy, Virginia Salmeron, Norma Herman, Gloria Escalante, Alice Gutierrez, Howard Watkins, Janie Munoz, Cristobal Perez, ?; back row: Bob Higgins, John Gant, ???, Ruben Lucero, Judy Evans, William Leifer, Bev ?, Elaine Harris